The Dynamics of the Election System during the New Order Period in Indonesia (Between Stability and Limitations of Democracy) - Pajarudin (Bulletin of Community Engagement, 2024)
This article examines the dynamics of Indonesia's electoral system during the New Order era, focusing on the tension between the pursuit of political stability and the limited application of democratic principles. During this period, elections were often tightly regulated to ensure the desired outcome for the regime, which tended to retain power. On the one hand, the New Order government sought to create political stability through strong control of the electoral process, including manipulation of results, restrictions on political participation and the use of a dominant party machine. On the other hand, this approach resulted in significant restrictions on the development of democracy in Indonesia, inhibiting genuine political representation and free speech. This article explores how the New Order electoral system contributed to political stability while also creating serious limitations on democratic practice, as well as its long-term impact on Indonesia's political development.